2004
DOI: 10.4049/jimmunol.173.11.6583
|View full text |Cite
|
Sign up to set email alerts
|

Pax5-Deficient Mice Exhibit Early Onset Osteopenia with Increased Osteoclast Progenitors

Abstract: Pax5 encodes BSAP, a member of the paired box domain transcription factors, whose expression is restricted to B lymphocyte lineage cells. Pax5−/− mice have a developmental arrest of the B cell lineage at the pro-B cell stage. We show here that Pax5−/− mice are severely osteopenic, missing 60% of their bone mass. The osteopenia can be accounted for by a >100% increase in the number of osteoclasts in bone measured histomorphometrically. This is not due to a lack of B cells, because other strains of B cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
54
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(57 citation statements)
references
References 43 publications
3
54
0
Order By: Relevance
“…Consistent with our results (Fig. 1A), however, no expression of Pax5 in osteoclasts and osteoblasts is detected, suggesting an indirect regulatory system (40). Given that bone metabolism is regulated not only by factors intrinsic to osteoblasts and osteoclasts but also by numerous extrinsic factors, the phenotypes observed in Pax5 mutant mice may be caused by regulatory mechanisms extrinsic to osteoblasts and osteoclasts.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Consistent with our results (Fig. 1A), however, no expression of Pax5 in osteoclasts and osteoblasts is detected, suggesting an indirect regulatory system (40). Given that bone metabolism is regulated not only by factors intrinsic to osteoblasts and osteoclasts but also by numerous extrinsic factors, the phenotypes observed in Pax5 mutant mice may be caused by regulatory mechanisms extrinsic to osteoblasts and osteoclasts.…”
Section: Discussionsupporting
confidence: 90%
“…It has been reported that Pax5-deficient mice exhibit osteopenia (25), a pathological condition in which osteoclasts are likely to be involved (39). Although Pax5 was detected only in the B cell lineage, and not in bone marrow macrophages nor in osteoclasts (40), the report nonetheless suggests that Pax5 or its related Pax family members may play a role in bone metabolism. In fact, the findings of a mutation in PAX6 in a human case with Darier disease, aniridia, and bone cysts implicate a possible role for PAX6 in bone remodeling with ATPA2 (30).…”
Section: Pax6 Expression During Rankl-induced Osteoclastogenesis-mentioning
confidence: 75%
See 1 more Smart Citation
“…Pax5 is shown to be expressed by the pro-B cells to the mature B cells in the hematopoietic system with a role to control the differentiation, function and identity of B lymphocytes, (25,26) whereas a low bone mass phenotype is seen due to the increased osteoclastic parameters, along with normal or slightly decreased osteoblastic parameters on histomorphometric analysis in Pax5 -/-mice. (12) Although neither the proliferative response nor the production of ALP is significantly different between cultured calvarial osteoblasts prepared from WT and Pax5-null mice throughout the culture period; indeed, Pax5 deficiency is shown to increase the number of osteoblastic precursors in bone marrows without affecting the number of mature osteoblasts in bones. (12) These in vivo findings in Pax5-null mice are apparently in disagreement with the present in vitro experimental results in preosteoblastic MC3T3-E1 cells with knockdown by siRNA and stable overexpression of Pax5.…”
Section: Discussionmentioning
confidence: 94%
“…(9,10) These Pax proteins are shown to play a pivotal role in organogenesis during embryonic development as transcription factors with restricted spatial and temporal expression patterns. (9,10) Although skeletal abnormalities are indeed seen in mice globally deficient of particular Pax proteins, including Pax1, (11) Pax5, (12) Pax7, (13) and Pax9, (14) little attention has been paid to a role of Pax family members in osteoblastogenesis. In the present study, therefore, we have attempted to show the possible involvement of the Pax family members in mechanisms underlying the regulation of osteoblastogenesis for bone formation and remodeling, using in vitro and in vivo experimental techniques.…”
Section: J Jbmrmentioning
confidence: 99%